Performance Analysis of Zakat Practices in Pati Regency (Case Study: The National Board of Zakat [BAZNAS] Pati Regency, Indonesia) - Fitriani . (International Journal of Zakat, 2018)
A crucial problem faced by Indonesia is its high poverty rate. One of the redistribution instruments that can be used to reduce poverty is zakat. The zakat potential of Pati Regency, Indonesia in 2016 was approximately Rp 20 billion, but the funds collected only amounted to around 9 percent of this figure (Rp 1.8 billion). This statistic shows that the management of zakat is not optimized, both in terms of its collection and distribution. This study aims to evaluate the performance of zakat practices, and the influenceof zakat on the welfare of mustahik (recipients of zakat) in Pati Regency, Indonesia. The research was conducted by means of a survey of 100 households of mustahik and interviews. The sampling method that used in this research was purposive sampling technique. Analysis of the result was undertakenusing by National Zakat Index (NZI) and Muti-Stage Weight Index Method. The result of this research show that the performance of zakat practices in Pati Regency is in the “less good” category with an index value of 0.392. Keywords: Poverty, National Zakat Index, Performance of Zakat Practices